The Impact of Museum Education post Covid-19: an integration of 4IR and Time Travel Method as teaching tools - Mlambo, Lesego Bridget (Cadernos do LEPAARQ (UFPEL), 2020)
Museum Education has been and continue to be a great support system for the school curriculum. It has a way of connecting with the classroom education even when school curriculum experiences curriculum changes due to seasonal, environmental and political changes. This paper therefore, investigates how museum education is affected by changes of the classroom education visa vee the school curriculum. The main focus of these changes will be around the integration of 4th Industrial Revolution (4IR) post the covid-19 in museum education as a response to the school curriculum. The school subject interest that probes between museum education and the school curriculum is around the History and subsequently the Archaeology subjects. The specific school curriculum mention for this paper is based on the South African Department of Education’s (DBE) 2018 Report of the History Ministerial Task Team in particular to the section of including Archaeology as a subject. The rationale behind the interest in this report is that it not only affects the teaching of History in the school classroom but also affects the teaching of History in the relevant South African museums. Resumo: A Educação em Museus foi e continua a ser um grande sistema de apoio ao currículo escolar. Tendo uma forma de se conectar com a educação em sala de aula, mesmo quando o currículo escolar passa por mudanças curriculares devido a mudanças sazonais, ambientais e políticas. Este artigo, portanto, investiga como a educação em museus é afetada por mudanças no vis-à-vis da educação em sala de aula e no currículo escolar. O foco principal dessas mudanças será em torno da integração da 4ª Revolução Industrial pós covid-19 na educação em museus como uma resposta ao currículo escolar. O interesse pela disciplina escolar que explora temas entre a educação museológica e o currículo escolar gira em torno das disciplinas de História e posteriormente de Arqueologia. A menção do currículo escolar específico para este artigo é baseada no Relatório do Departamento de Educação da África do Sul (DBE) 2018 da Equipe de Tarefa Ministerial de História, em particular para a seção de incluir Arqueologia como um assunto. A justificativa por trás do interesse neste relatório é que ele não afeta apenas o ensino de História na sala de aula escolar, mas também afeta o ensino de História em relevantes museus sul-africanos.